Aftershock performance evaluation of shear wall structures with replaceable coupling beam including low-cycle degradation. (October 2022) - Gong, Nan; Li, Peizhen; Shan, Jiazeng
Abstract: Mainshock-damaged shear wall structures equipped with replaceable coupling beams (RCB) may be vulnerable to aftershock sequences due to damage accumulation and structural deterioration. An aftershock performance evaluation framework and an analytical fatigue hysteretic model are first proposed. Then, the mainshock incremental dynamic analysis (IDA) and the aftershock fragility analysis are performed on the mainshock-damaged structures. In addition, the replacement of damaged RCBs with different strategies is further discussed. Representative results indicate that the aftershock may be relatively destructive considering the degradation behavior of mainshock-damaged RCBs. Meanwhile, the timely replacement of damaged RCBs may recover the structural integrity and mitigate the potential aftershock-induced damages.